A modified method of immediate occlusal loading using a reinforced framework denture: A case report - Mazaro, José Vitor Quinelli [UNESP]; Vedovatto, Eduardo [UNESP]; Gennari Filho, Humberto [UNESP]; Pellizzer, Eduardo Piza [UNESP] (My University, 2009)
The technique presented in this article presents a protocol for treatment that reduces the time required for the fabrication and placement of an implant supported prosthesis. It also offers improved patient comfort at a lower cost when compared to conventional technology.
Keywords: acrylic acid resin; biomedical and dental materials; comparative study; dental equipment; denture; instrumentation; methodology; middle aged; tooth implantation; tooth prosthesis; Acrylic Resins; Dental Abutments; Dental Implantation, Endosseous; Dental Implants; Dental Materials; Dental Prosthesis, Implant-Supported; Denture Design; Denture Retention; Denture, Complete, Immediate; Denture, Complete, Lower; Middle Aged; Rubber Dams